Towards Understanding the Concept of Fatwa on Medical Treatment Involving Forbidden Sources: Tinjauan Terhadap Pemahaman Konsep Fatwa dalam Rawatan Perubatan yang Melibatkan Sumber-Sumber Haram - Azahar, Afifi; Mohammad, Firdaus; Mohamad, Ahmad (KATHA- The Official Journal of the Centre for Civilisational Dialogue, 2024)
The number of patients is believed to be increasing each year due to various diseases affecting a portion of the population, leading to an urgent need for modern medicines to treat patients in this country. However, an issue arises due to the use of forbidden substances such as pork, toxins, alcohol, and the like for medicinal purposes, despite Islam prohibiting the use of such substances. Therefore, this article aims to discuss the legality of treatment using forbidden sources and establish guidelines for its use from the perspective of Islam. This study employs qualitative methods and content analysis. Information sources are obtained from books, theses, and journal articles to compile a detailed study, subsequently analyzed descriptively. The study finds that the use of forbidden sources for medical purposes is permissible to save lives in emergency situations, subject to specific conditions. Keywords: Treatment, Disease, Islam, Emergency, Forbidden.